Vanadium exposure exacerbates allergic airway inflammation and remodeling through triggering reactive oxidative stress - Tu, Wei; Xiao, Xiaojun; Lu, Jiahua; Liu, Xiaoyu; Wang, Eryi; Yuan, Ruyi; Wan, Rongjun; Shen, Yingchun; Xu, Damo; Yang, Pingchang; Gong, Miao; Gao, Peisong; et al. (Frontiers in Immunology, 2023)
Background Metal components of environmental PM2.5 are associated with the exacerbation of allergic diseases like asthma. In our recent hospital-based population study, exposure to vanadium is shown to pose a significant risk for current asthma, but the causal relationship and its underlying molecular mechanisms remain unclear. Objective We sought to determine whether vanadium co-exposure can aggravate house dust mite (HDM)-induced allergic airway inflammation and remodeling, as well as investigate its related mechanisms. Methods Asthma mouse model was generated by using either vanadium pentoxide (V2O5) or HDM alone or in combination, in which the airway inflammation and remodeling was investigated. The effect of V2O5 co-exposure on HDM-induced epithelial-derived cytokine release and oxidative stress (ROS) generation was also examined by in vitro analyses. The role of ROS in V2O5 co-exposure-induced cytokine release and airway inflammation and remodeling was examined by using inhibitors or antioxidant. Results Compared to HDM alone, V2O5 co-exposure exacerbated HDM-induced airway inflammation with increased infiltration of inflammatory cells and elevated levels of Th1/Th2/Th17 and epithelial-derived (IL-25, TSLP) cytokines in the bronchoalveolar lavage fluids (BALFs). Intriguingly, V2O5 co-exposure also potentiated HDM-induced airway remodeling. Increased cytokine release was further supported by in vitro analysis in human bronchial epithelial cells (HBECs). Mechanistically, ROS, particularly mitochondrial-derived ROS, was significantly enhanced in HBECs after V2O5 co-exposure as compared to HDM challenge alone. Inhibition of ROS with its inhibitor N-acetyl-L-cysteine (NAC) and mitochondrial-targeted antioxidant MitoTEMPO blocked the increased epithelial release caused by V2O5 co-exposure. Furthermore, vitamin D3 as an antioxidant was found to inhibit V2O5 co-exposure-induced increased airway epithelial cytokine release and airway remodeling. Conclusions Our findings suggest that vanadium co-exposure exacerbates epithelial ROS generation that contribute to increased allergic airway inflammation and remodeling.